2018
DOI: 10.1080/09640568.2018.1447444
|View full text |Cite
|
Sign up to set email alerts
|

For what it's worth: evaluating revealed preferences for green certification

Abstract: In a case study that examines the outcomes of a flexible information-based policy, we observe how organizations obtain Leadership in Energy and Environmental Design certification. We use a regression discontinuity analysis to identify practices used to upgrade certification tiers. This analysis reveals preferences for green certification strategies and, we argue, intimates the perceived motivations for green certification. We distinguish practices that potentially confer private gains through returns to effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Given a certification scheme, the sender chooses either payoff E[q | m] − c from applying for certification or E[q | "uncertified " ] from not applying. 7 Our equilibrium concept is Perfect Bayesian Equilibrium, so given any grading scheme, receiver beliefs must be consistent with sender choices and follow Bayes Rule, and sender choices must be best responses to receiver beliefs. If, for a given grading scheme and cost c , there exists an equilibrium in which any positive measure of sender types applies for certification, we call that scheme feasible.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a certification scheme, the sender chooses either payoff E[q | m] − c from applying for certification or E[q | "uncertified " ] from not applying. 7 Our equilibrium concept is Perfect Bayesian Equilibrium, so given any grading scheme, receiver beliefs must be consistent with sender choices and follow Bayes Rule, and sender choices must be best responses to receiver beliefs. If, for a given grading scheme and cost c , there exists an equilibrium in which any positive measure of sender types applies for certification, we call that scheme feasible.…”
Section: The Modelmentioning
confidence: 99%
“…A referee suggested that, if transfers were allowed, the certifier might reimburse senders depending on their quality while maintaining a balanced budget. 7 For simplicity we assume that there is only one certifier to apply to. Since the goal of a certifier is to maximize information to consumers, it will not engage in competition that worsens information, e.g., by providing exact grading to firms with very high quality to draw them away from (and destabilize) a pass-fail certifier.…”
Section: The Modelmentioning
confidence: 99%
“…The LEED standard does not require monitoring of actual user behavior and energy consumption. While more rigid standards based on long-term energy monitoring are possible, they are only rarely implemented in green buildings (Flowers et al, 2019). Few measures are in place to check LEED buildings' actual energy consumption.…”
Section: Sustainable Real Estatementioning
confidence: 99%
“…The standard strictly prescribes a minimum air quality threshold and prohibits certain pollutants, but also rewards improvements beyond that prescription. As a result, indoor air quality improvements have been voluntarily adopted (Wu et al, 2016), particularly in buildings serving vulnerable populations, such as schools and hospitals (Flowers et al, 2019). These standards may even have diffused to non-certified buildings (Blackburn et al, 2020).…”
Section: Sustainable Real Estatementioning
confidence: 99%
“…For each improvement made, the building earns “credits” or points toward a LEED score, measured continuously. Descriptive studies of participation in LEED reveal that common credits used for certification include improvements to a building envelope's energy efficiency, increased access to natural and daylighting inside the building, and provision of parking spaces to facilitate low‐energy and alternative transit (Da Silva & Ruwanpura, 2009; Flowers, Matisoff, & Noonan, 2019; Wu, Mao, Wang, Song, & Wang, 2016). After receiving 40% of total possible credits, a building can be certified.…”
Section: Empirical Context: Racing To the Top In Green Buildingmentioning
confidence: 99%